A Commonwealth of the people : time for urgent reform (Commonwealth Secretariat LondonGB, 2011)
Seeks to identify ways in which the Commonwealth could improve its activities in accordance with a set of priorities for which it is best suited to serve its member states and to contribute to global well-being. This report and the action that will be taken upon its recommendations constitite a unique opportunity to arrest a decline in the Commonwealth's influence and significance, and to reform it so that it plays a leading and beneficial role in the future.
Keywords: COMMONWEALTH